Guidelines on strategies for the universal implementation of videolaryngoscopy - Manuel A., Gómez-Ríos; Andre A.J, Van Zundert; Alistair F., McNarry; J. Adam, Law; Andy, Higgs; Samuel Ern Hung, Tsan (European Society of Anaesthesiology and Intensive Care, 2025)
OBJECTIVE The Airway Section of the Spanish Society of Anaesthesiology, Resuscitation, and Pain Therapy (SEDAR), the Spanish Society of Emergency Medicine (SEMES), the Latin American Federation of Emergency Medicine (FLAME) and an international group of airway experts (IAG) aimed to establish multidisciplinary recommendations advocating for the universal use of videolaryngoscopy (VL) in both emergency and planned care settings.